Quantum Chemical Investigation of C12 and C6 Position of Oseltamivir Sialidase Antiviral Inhibitor - Krishnan Chandrasekaran (Journal of Applied Pharmaceutical Science, 2015)
The ab initio and DFT investigation of C12 & C6 position of oseltamivir sialidase inhibitor reveals that the absence of pyranose oxygen ring in the inhibitor structure drastically increases binding affinity of the inhibitor in relation to the pyranose based inhibitors. The investigation further reveals that the methyl and ethyl group at the C12 position have substantial binding affinity due to their inherent hyperconjugative and charge transfer effects between C4 and C13 bond. The analysis at C6 position of oseltamivir inhibitor discloses that the methyl amine group increases the binding affinity due to their strong hydrogen bonding tendency with the vicinity receptors. Hence, the investigation validates that the 12-methyl-oseltamivir, 12-ethyl-oseltamivir and 6-methylamine-oseltamivir inhibitor become the potential candidate for the development effective sialidase antiviral inhibitors.
Keywords: Oseltamivir, Sialidase inhibitors. Binding affinity, influenza virus.